2008
DOI: 10.1016/j.biopsycho.2007.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Incentive motivation is associated with striatal dopamine asymmetry

Abstract: Dopamine plays an important role in modulating incentive motivation, expressed behaviorally as approach behavior. EEG studies report association between approach behavior and asymmetric pattern of activation in anterior cortical regions (as measured by the inverse of EEG alpha power). Therefore, individual differences in incentive motivation may reflect asymmetries in dopaminergic systems. We examined this hypothesis by studying the relationship between self-reported degree of incentive motivation, and asymmet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
58
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 21 publications
7
58
3
Order By: Relevance
“…This right-greater-than-left asymmetry has been reported in previous studies where healthy people were found to have the right-greater-than-left asymmetry in D 2 receptor and DAT availability in the caudate (Laakso et al 2001;Tomer et al 2008). Moreover, several imaging studies in opioid or methamphetamine dependent subjects and healthy controls also found a slight right-great-than-left asymmetry in DAT levels in the striatum Liu et al 2013;Shi et al 2008;Yuan et al 2014).…”
Section: Discussionsupporting
confidence: 82%
“…This right-greater-than-left asymmetry has been reported in previous studies where healthy people were found to have the right-greater-than-left asymmetry in D 2 receptor and DAT availability in the caudate (Laakso et al 2001;Tomer et al 2008). Moreover, several imaging studies in opioid or methamphetamine dependent subjects and healthy controls also found a slight right-great-than-left asymmetry in DAT levels in the striatum Liu et al 2013;Shi et al 2008;Yuan et al 2014).…”
Section: Discussionsupporting
confidence: 82%
“…Lateralization effects have been reported in human PET studies of the dopamine system (e.g., refs. 51 and 52) and also with respect to the association of these dopamine measurements with reward and motivation (53,54). However, results in the present study were derived from right-handed participants alone, and all reported correlations remained significant when controlling for dopamine measures from right and left striata.…”
Section: Limitationsmentioning
confidence: 47%
“…The rACC projects to the medial part of the ventral striatum (Kunishio & Haber, 1994), and recent findings suggest a role of the ACC and the ventral striatum in aE theta effects (see, e.g., O'Gorman et al, 2006, for effects within the caudate). Moreover, studies assessing dopamine receptor D2/3 availability have reported that the left ventral striatum correlates strongly with measures of extraversion (e.g., Tomer, Goldstein, Wang, Wong, & Volkow, 2008). Individual differences in ventral striatum activity may not only be related to resting delta/theta activity in the rACC, as previously shown (Wacker et al, 2009), but also contribute to the EEG posterior-anterior difference by modulating, for example, the insula and the posterior .42** Fig.…”
Section: Functional Significance Of Posterior Versus Anterior Theta: mentioning
confidence: 72%